Technology Assessment in a Globalized World Facing the Challenges of Transnational Technology Governance - Hennen, Leonhard; Hahn, Julia; Ladikas, Miltos; Lindner, Ralf; Peissl, Walter; van Est, Rinie (Springer Nature, 2023)
This open access book explores the relevance of the concept of technology assessment (TA) on an international and global level. Technologies play a key role in addressing global challenges such as climate change, population aging, digitization, and health. At the same time, their use increases the need for coordinated action and governance at the global level in the field of science, technology and innovation (STI). Featuring case studies on STI fields such as energy, biotechnology, artificial intelligence, and health technology, as well as TA activities at the national and international levels, this book reflects on the challenges and opportunities of global technology governance. It also provides an in-depth discussion of current governmental STI cultures and systems, societal expectations, and the policy priorities needed to achieve coordinated and effective STI intervention in policymaking and public debate at the global level. Lastly, the book promotes the establishment of a forum for a truly global dialogue of TA practitioners, fostering the articulation of their needs, knowledge and perspectives.